THE UNREQUITED LOVE AS REFLECTED IN WILLIAM BLAKE’S “LOVE’S SECRET” - Risthania, Olivia Fergie (LANTERN (Journal on English Language, Culture and Literature), 2014)
The purpose of this final academic paper is to describe the love story which tells sadness in William Blake’s “Love's Secret”. The writer adopts Erich Fromm’s theory of unrequited love from The Art of Loving. This final academic paper concerns intrinsic and extrinsic side of the poem. In the intrinsic side, the writer discusses about the existing diction and figurative language such as denotation and connotation and imagery to understand the true meaning of the poem. The extrinsic side, the writer discusses about unrequited love. The writer used library research, note-taking and internet browsing for collecting the data. The result is that love does not only bring happiness but also deep sadness for the speaker of the poem as unrequited love which is reflected in “Love's Secret”. So, it succeeds in bringing the readers to feel what the speaker feels.